Crack-induced electrical resistivity changes in cracked CNT-reinforced composites. (April 2020) - Rodríguez-Tembleque, L.; García-Sánchez, F.; García-Macías, E.; Buroni, F.C.; Sáez, A.
Highlights: Formulation to quantify electrical resistivity changes in CNT-RC sensors due to cracks. The efficiency of the strip-like sensors is affected by three parameters. The strain gradients caused by the crack affect the resistivity of the plate. The electric permeability of the crack has revealed as the key parameter. Moreover, the severity of the damage also affect to the efficiency of the sensor. This numerical framework could be extended for self-sensing structures developments. Abstract: Carbon nanotube (CNT)-reinforced composites exhibit a piezoresistive behavior that permits their use as sensors in novel structural health monitoring (SHM) applications, by measuring the electrical resistivity change of the CNT modified laminate. However, the presence of cracks in such composite materials may not only compromise their structural integrity, but may as well alter their capability to act as reliable piezoresistive sensors. In this paper, we conduct a numerical study aimed at quantifying how the presence of cracks in reinforced polymer composites does influence their electrical conductivity and, consequently, their sensor performance. To this end, the electromechanical constitutive properties of the composite are determined by a mixed micromechanics approach that allows characterizing both the elastic properties and the strain-induced alterations in the overall electrical conductivity of the CNT-reinforced composite. The strain response of the cracked composite domain is accurately determined by means of a dual Boundary Element (BE) approach. Electrical conductivity in the cracked composite follows from its computed strain state at each point in the domain. Subsequently, the resulting non-homogeneous electrical conductivity problem is solved using a finite differences scheme that also accounts for semipermeable crack-face electrical boundary conditions. Several parametric studies are conducted to illustrate the influence of various crack geometries in the piezoresistive behavior of CNT-reinforced composites at varying CNTs concentrations.